Forage Production and Nutrient Content of Different Elephant Grass Varieties Cultivated with Indigofera zollingeriana in an Intercropping System - A. Ernawati; L. Abdullah; I. G. Permana; P. D. M. H. Karti (Tropical Animal Science Journal, 2023)
A proper planting system and efficient management are needed to cultivate forage effectively. Therefore, this research aimed to evaluate forage production and nutrient content of different elephant grass varieties grown with Indigofera in the intercropping system and were harvested at different intervals of defoliation. The research was conducted in the dry and rainy seasons using a randomized block design with 3 factors (2x2x2) and 4 replications. The first factor was two different elephant grass varieties consisting of cv. Pakchong and Taiwan, the second factor was the planting pattern, including intercropping and monoculture, while the third factor was harvesting age, comprising 50 days and 60 days. The results showed an interaction effect between grass varieties, planting patterns, and harvesting ages. Intercropping the Pakchong varieties with Indigofera and harvesting at 60 days produced the highest forage fresh weight and DM production, ADF as well as NDF contents and yields, CP yield, and the highest carrying capacity (p<0.05) according to DM intake. When harvested at 50 days, Indigofera increased the protein content of forage, but this effect did not occur when it was harvested at 60 days. Furthermore, nutrient yields were not affected by interactions of three factors in the rainy season (p>0.05), but in the dry season, the highest ash and CP yields were produced by the Pakchong variety intercropped with Indigofera and harvesting at 60 days. The highest ADF and NDF yields were obtained from the Taiwan varieties grown in monoculture and harvested at 60 days. Based on the results, it was concluded that the two varieties of elephant grass could be cultivated with Indigofera in the intercropping system and harvesting time of 60 days will produce the highest nutrient yield and carrying capacity.